Covid-19 and Human Rights: The Capture of the Fulfilment of Rights During the Covid Outbreaks - Anis Widyawati; Rasdi Rasdi; Ridwan Arifin; Septhian Eka Adiyatma (Unnes Law Journal, 2020)
Fulfilment and protection of human rights in all aspects is a form of Constitutional Rights for Citizens that must be fulfilled by the State. Basic human rights also under no circumstances can be reduced even deprived. However, the fact is, human rights regulated in various laws and regulations in Indonesia have not been maximally implemented. The fulfilment and protection of human rights also faces its own challenges in implementing it in certain cases, for example disasters such as Pandemic Covid-19. Various legal instruments, both central and regional, were created to deal with and resolve the Covid-19 Pandemic problem. This study aims to examine the implementation of the fulfilment and protection of human rights in special situations such as Covid-19 Pandemic. This research is limited to the Semarang City area. This study wanted to find out and analyze various aspects of law and human rights in the implementation of various policies related to Covid-19 in the City of Semarang. This study seeks to find challenges and problems in the protection and fulfilment of human rights in the city of Semarang in the Covid-19 Pandemic. The method in this study uses empirical research, where researchers directly go to the field. The planned data was obtained from various related agencies in the city of Semarang, the community, and related NGOs. This research will assist the government in mapping human rights fulfilment policies in national disaster situations in this case the Covid-19 Pandemic.